Barriers to Weight Loss and Physical Activity, and Coach Approaches to Addressing Barriers, in a Real-World Adaptation of the DPP Lifestyle Intervention: A Process Analysis. Issue 6 (December 2019) - Delahanty, Linda M.; Trief, Paula M.; Cibula, Donald A.; Weinstock, Ruth S.
Purpose: The purpose of this study is to identify barriers to weight loss and physical activity, as well as approaches used by coaches, in a real-world, community sample of adults with metabolic syndrome (at risk for type 2 diabetes) who participated in a Diabetes Prevention Program (DPP)–adapted weight loss intervention and compare findings to data from the screened and highly selected DPP sample. Methods: SHINE (Support, Health Information, Nutrition, and Exercise) was a telephonic DPP adaptation. Primary care staff delivered the DPP curriculum, and lifestyle coaches provided monthly direction to achieve weight loss. For this substudy, barriers to weight loss and physical activity described by participants, as well as approaches coaches used to address them, were gathered. Groupings of barriers (DPP defined) were analyzed in relation to demographic characteristics and compared to data from the DPP sample. Results: Top weight loss barriers were problems with self-monitoring, too little physical activity, internal thought/mood cues, vacation/holidays, and social cues. Percentages reporting a barrier were much higher in SHINE. Top physical activity barriers were problems with self-monitoring, access/weather, time management, aches/pains, and vacation/holidays. These did not correspond closely to DPP data. Coaches used problem solving, self-monitoring skills review, increased physical activity, and motivational strategies. SHINE coaches were more likely than DPP coaches to use alternative approaches. Conclusions: Barriers to weight loss and physical activity in a community sample of persons at risk for diabetes occurred at much higher rates than in the highly screened DPP sample. Training coaches in a variety of patient-centered approaches may maximize their positive impact.